Optimal configuration of hybrid PV-generator (diesel/GPL) for a decentralized production of electricity in Algeria - Amara Mohamed; Zablah Abdelkader; Bouanane Abdelkrim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The absence of electricity in rural areas is one of the major challenges faced by many developing countries like Algeria. This work has been devoted to the design of an off-grid renewable hybrid power system for a rural village in the region of Tindouf located in south Algeria. The main objective of this study is to determine the optimum size of the hybrid power system able to fulfill the requirements of 709 kWh/day primary load with 66 kW peak load for a remote area of 230 households. This study is based on simulation and optimization of a (PV-Diesel) and (PV-GPL) hybrid system with a technical-economic analysis. Simulation results showed that electrifying using a PV/GPL generator hybrid system is more advantageous when compared to the PV/diesel generator hybrid system as it has lower operating costs and emissions. The comparison is based on per unit cost of electrical energy production, operating cost of conventional fossil fuel-based energy sources and pollutants gases reduction.